2010
DOI: 10.1016/j.rfe.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Project finance as a driver of economic growth in low‐income countries

Abstract: This study investigates the role of project finance as a driver of economic growth. We hypothesize that project finance is beneficial to the least developed economies as it compensates for any lack of domestic financial development. The contractual structure unique to project finance should lead to better investment management and governance. Investigating 90 countries from 1991 to 2005, we find support for our hypothesis. Project finance indeed fosters economic growth and this effect is strongest in low-incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 84 publications
(90 reference statements)
3
24
0
2
Order By: Relevance
“…According to the Dealogic Projectware Database, global project volume more than tripled from 2003 to 2011, from US$113.4 billion to US$408.3 billion, with Asia being the fastest growing regional market. And project finance has become almost equally widespread in less developed countries as a facilitator of economic growth (Kleimeier and Versteeg, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Dealogic Projectware Database, global project volume more than tripled from 2003 to 2011, from US$113.4 billion to US$408.3 billion, with Asia being the fastest growing regional market. And project finance has become almost equally widespread in less developed countries as a facilitator of economic growth (Kleimeier and Versteeg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite justified criticism of ex-post development effects and the distribution of wealth (Arndt et al 2012;Lenz et al 2017), PF has allowed developing economies to construct infrastructure projects, which would not have been possible through public funding (Brealey et al 1996;Kleimeier and Versteeg 2010;La Cour and Müller 2014). The critical views on PF also underline the pressing need for further research on PF.…”
Section: History and Market For Project Financementioning
confidence: 99%
“…Kleimeier and Versteeg (2010) argued that the contractual structure unique to project finance engenders better investment management. Their empirical results showed that project finance compensates for lack of domestic financial development, particularly in less-developed economies where governance mechanisms are weak.…”
Section: Project Financementioning
confidence: 99%